Oxidative damage to lipids improves with Omega-5 fatty acid supplementation treatment in patients with severe alcoholic hepatitis - Moisés Martínez-Castillo; Jacqueline Cordova-Gallardo; Abigail Hernandez-Barragan; Marisela Hernández-Santillán; Diana Mungía-Ramos; Froylan Martínez-Sánchez; Daniel Santana-Vargas; Gabriela Gutiérrez-Reyes (Annals of Hepatology)
Introduction and Objectives: Chronic and excessive alcohol consumption causes alcoholic liver disease (ALD). Alcoholic hepatitis (AH) is a severe clinical event that develops in patients with ALD and active alcohol consumption, and it has a high mortality rate within 30 days. Inflammation and redox imbalance play a crucial role in promoting the dysfunction of hepatocytes and reducing patient survival. Glucocorticoids have a transient beneficial effect in AH; however, it is necessary to understand the effect of antioxidant therapy in this pathology. To evaluate oxidative stress of lipids in patients with alcoholic hepatitis whose treatment included Omega-5 Materials and Patients: The randomized, double-blind clinical study included two groups of patients (men and women) with severe alcoholic hepatitis: 1) Patients treated with Prednisone (40 mg/day) + oral administration of Omega-5 (0.64 g/day) (n=20; 10% women and 90% men), and 2) Prednisone + Placebo group (n=20; 15% women, 85% men). Both groups received treatment for 28 days. Alcohol consumption was calculated in g/day. Biochemical and hematological laboratory test were performed. The MELD, Glasgow, ABIC, and Lille scales were evaluated, as well as serum levels of lipid oxidation through malondialdehyde (MDA) at 7, 14, and 28 days. The data was analyzed by Kruskal-Wallis, Mann-Whitney U and ANOVA statistical tests by SPSS v.22, significance of p<0.05. Results: Both groups had similar characteristics; there was no difference in severity and alcohol consumption. After 7 days of treatment, both groups of patients showed similar levels of MDA, with the highest determination of MDA observed at this point. However, a reduction in serum MDA levels was observed at 14 days (5%) in the Omega-5 group; similarly, a 22% reduction in MDA was observed at 28 days. In contrast, the placebo group showed a continuous increase in MDA levels: 19.6% and 35% at 14 and 28 days, respectively. However, there were no statistical differences, indicating the need for further studies to evaluate changes in MDA levels over six months, as well as the effects of different doses and Omega-5supplementation time. Conclusions: The oral administration of Omega-5 fatty acid in combination with prednisone can reduce oxidative stress of lipids at the systemic level. The use of antioxidant therapy as an adjuvant may improve the redox state and inflammation, which could decrease infectious events and, consequently, mortality in alcoholic hepatitis.